Peer Relationships and Mass Media with Premarital Sex Behavior Young Women at Al-Jihad Surabaya Islamic Boarding School - Nur Ayda, Zulva; Afridah, Wiwik (PROCEEDING SURABAYA INTERNATIONAL HEALTH CONFERENCE 2019, 2020)
The low level of knowledge about reproductive health has caused many problems regarding premarital sex behavior in Islamic boarding schools. This study aims to analyze peer relationships and mass media with premarital sexual behavior of young women at the Surabaya Al-Jihad Islamic Boarding School. The type of research used is an analytical survey with aapproach cross-sectional. The study was conducted in March 2019 with a sample of 137 respondents with a simple random sampling technique. The research instruments used were questionnaires. Data analysis usingtest chi square. The results showed that most (59.9%) had peers who influenced negatively, most (51.8%) obtained information through electronic media, and most (73.0%) had premarital sex behavior was not dangerous. The results showed that there was a significant relationship between peers and female sex behavior (p = 0.004), and there was a significant relationship between mass media and premarital sexual behavior of young women (p = 0.040). It is recommended for Islamic boarding schools to be able to provide information centers and reproductive health services in order to get complete and precise information.